Bringing into focus the central domains C3-C6 of myosin binding protein C - Doh, Chang Yoon; Schmidt, Alexandra V.; Chinthalapudi, Krishna; Stelzer, Julian E. (Frontiers in Physiology, 2024)
Myosin binding protein C (MyBPC) is a multi-domain protein with each region having a distinct functional role in muscle contraction. The central domains of MyBPC have often been overlooked due to their unclear roles. However, recent research shows promise in understanding their potential structural and regulatory functions. Understanding the central region of MyBPC is important because it may have specialized function that can be used as drug targets or for disease-specific therapies. In this review, we provide a brief overview of the evolution of our understanding of the central domains of MyBPC in regard to its domain structures, arrangement and dynamics, interaction partners, hypothesized functions, disease-causing mutations, and post-translational modifications. We highlight key research studies that have helped advance our understanding of the central region. Lastly, we discuss gaps in our current understanding and potential avenues to further research and discovery.